2003
DOI: 10.1002/ijc.11227
|View full text |Cite
|
Sign up to set email alerts
|

Altered methylation of multiple genes in carcinogenesis of the prostate

Abstract: The methylation status of 7 genes was examined in four cell lines, 36 samples of benign prostatic hyperplasia (BPH), 20 samples of prostatic intraepithelial neoplasia (PIN) and 109 samples of prostate cancer (PCa), using methylationspecific PCR (MSP): the pi-class glutathione S-transferase (GSTP1), retinoic acid receptor beta 2(RAR␤2), androgen receptor (AR), death-associated protein kinase (DAPK), tissue inhibitor of metalloproteinase-3 (TIMP-3), O 6 -methylguanine DNA methyltransferase (MGMT), and hypermethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
2
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(125 citation statements)
references
References 38 publications
5
114
2
2
Order By: Relevance
“…Consistent with our results, other studies have also described quantitatively much less promoter methylation of GSTP1 in BPH and histologically normal tissue (from tumour containing prostates) than in cancer specimens (Jeronimo et al, 2001;Yamanaka et al, 2003). Although every effort was taken to ensure that tissue was only procured from within pathologically identified areas, we cannot rule out the possibility that minute amounts of occult carcinoma or HGPIN may have been present in some of the benign specimens.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our results, other studies have also described quantitatively much less promoter methylation of GSTP1 in BPH and histologically normal tissue (from tumour containing prostates) than in cancer specimens (Jeronimo et al, 2001;Yamanaka et al, 2003). Although every effort was taken to ensure that tissue was only procured from within pathologically identified areas, we cannot rule out the possibility that minute amounts of occult carcinoma or HGPIN may have been present in some of the benign specimens.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies showed that HIC-1 was commonly hypermethylated and transcriptionally inactivated in leukemia, medulloblastoma, and cancers of breast, prostate, and uterine cervix. 23,[41][42][43][44] In the present study, HIC-1 was the most frequently methylated gene among the panel of genes studied in both hydatidiform moles as well as in choriocarcinoma. This indicated that methylation of HIC-1 might be an early event involved in the pathogenesis of GTD.…”
Section: Figurementioning
confidence: 83%
“…DNA methylation patterns in CpG islands of tumor suppressor genes p16 (20), BRCA1 (21), RASSF1A (22), ER-␣ (23), TMS1 (24), TIMP and GSTP1 (25), Twist (26), AR (27), and hMLH1 (28) were determined by chemical modification with sodium bisulfite. The primer sequences used have all been reported previously and can be found in the report referenced after each gene.…”
Section: Methodsmentioning
confidence: 99%